Hai trăm năm mươi 250 cases in clinical medicine - Baliga, R. R. (Elsevier/Saunders, 2012)
A new, fully updated edition of Baliga's very popular collection of short cases arranged by clinical area, emphasising the key diagnostic features of clinical conditions as commonly presented in the short-case part of the Final MB and MRCP examinations. Also included are likely instructions or commands expected from the examiner for each condition, and the key points which the candidate must tell the examiner. A must-have for the final-year undergraduate and trainee doctor